การศึกษาสมรรถนะของอุปกรณ์ทำความเย็นแบบสัมผัสและระเหยโดยตรง - พรชัย สุวัฒน์เมฆินทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
A direct contact evaporative cooler has been widely used in various agricultural sectors such as green-houses or animal barns. It has many advantages such as reducing ventilating air temperature, low cost of installation, operation and maintenance when compared with the other type of environmental control systems. This system, however, has a major deficiency particularly in lowering supply air temperature when the ambient air has high relative humidity. This research studied a performance of a direct contact evaporative cooler for both adiabatic and non-adiabatic types. Two set of experiments were conducted. The first one was conducted to analyze the effects of water mass flow rates and also the effect of air velocity on the adiabatic system. The second one was conducted to find the effect of various inlet water temperatures and water-to-air mass flow ratios on nonadiabatic system. The results showed that in the adiabatic system the water mass flow rates had a little effect on the outlet air temperature while the air velocity has much greater effect. The use of low air velocity would assist in lowering outlet air temperature. In the nonadiabatic system the temperature of the inlet water has large effect on the outlet air temperature. The lower inlet water air temperature had a remarkable low outlet air temperature. The important factor effecting outlet air temperature is the water-to-air mass flow ratio. It was also found that increasing water-to-air mass flow ratio could lower the outlet air temperatures. In addition, we also found that at a fixed inlet water temperature using similar water-to-air mass flow ratio would produce a similar outlet air temperature.